(untitled) - Griswold, Norman E (Lexington, Massachusetts, 1984)
This book is divided into chapters, each of them contains sections called Overview of the Chapter , Suggestions for Study, Words Frequently Mispronounced, Performance Goals, and Self-Help Test. The Overview contains a brief description of the chapter's contents. The Suggestions gives suggestions for special study emphasis, correlates some topics with those in previous chapters, and points out potential difficulties or misunderstandings that may arise and how to avoid them. The Words Frequently Mispronounced appears only when pronounciation aids which are provided in the form of a phonetic system. The performance goals points out the rules, laws, and concepts, and describes only the most essential things to be memorized. The Self-Help Test contains very few numerical problems; the text has this type of problem (with answers) at the end of the chapters; the answers are accompanied by brief explanations
Keywords: chemistry